The level of group taxation in South Africa, corporate roll over provisions, key considerations, and challenges - Ngwenya, Eunice (University of the Witwatersrand, Johannesburg, 2024)
Group taxation refers to a tax system that allows offsetting of losses against profits within qualifying related companies as well as the ability to transfer assets to fellow group companies without triggering any tax liability. Without group taxation, inefficiencies arise whereby at the first instance, some companies within a group may incur a large tax liability while others have large assessed losses that cannot be utilized because such companies continue to incur losses. Secondly, very often companies go through a reorganization of some sort which may include transfer of assets to other entities within the group where synergies may have been identified. These types of transactions often result in significant tax leakages if inter-group transfer of assets which is legally acceptable in terms of other legislations such as the Companies Act 71 of 2008 (“Companies Act”), is not allowed to be on a tax neutral basis. In South Africa, however, group taxation is limited to roll over relief provisions contained in sections 41-47 of the Income Tax Act 58 of 1962 (“the Income Tax Act” or “the Act”), if conditions detailed therein are complied with. So far, there is no other group taxation is allowed. This study seeks to define what group taxation is and what would be achieved if it is implemented, it also outlines the impact of the lack thereof. It examines the legal and regulatory implications of transactions covered by the roll over relief provisions with specific focus being the Income Tax Act, the Value Added Tax Act 89 of 1991 (“VAT Act”), the Companies Act, Transfer Duty Act 40 of 1949 (“Transfer Duty Act”) and Securities Transfer Tax Act 25 of 2007 (“STT Act”). The study also looks at the detailed requirements to be met for each roll over provision to apply in terms of the Income Tax Act, the applicable exclusions and anti- avoidance provisions. It assesses how the roll over provisions are harmonized across the Income Tax Act, the VAT Act, other tax Acts and the Companies Act.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; group companies; roll-over relief provisions; asset for share transaction; substitutive share for share transaction; amalgamation transaction; inter-group transaction; unbundling transaction; liquidation distribution; roll-over reliefprovisions; capital gains; revenue income; ring-fencing; going concern; SDG-8: Decent work and economic growth